Hexamethyldisilazane-iodine induced intramolecular dehydrative cyclization of diamides: a general access to natural and unnatural quinazolinones - Kshirsagar, Umesh A.; Mhaske, Santosh B.; N. P. Argade (Tetrahedron Letters, 2007)
A simple and efficient general approach to various quinazolinone scaffolds, including peptidomimetic examples, has been demonstrated by employing HMDS/I-2 for the intramolecular dehydrative cyclization of diamides. The protecting groups -Boc, -Fmoc and -Cbz tolerated the present reaction conditions and we did not observe any racemization. The present protocol has also been used as a key step for the efficient four-step syntheses of the naturally occurring quinazolinones, sclerotigenin, (-)-circumdatin-F and (-)-fumiquinazoline-F. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: diamides; HMDS/I-2; intramolecular dehydrative cyclizations; natural and unnatural quinazolinones; synthesis